Fair shares and selective attention - Dianna Amasino; Davide Pace; Joël J. van der Weele (Tinbergen Institute, 2021)
Attitudes towards fairness and redistribution differ along socio-economic lines, resulting in political conflict. To understand the formation of such views and find levers to affect them, we study the role of attention. In a large online experiment, we investigate how subjects allocate their visual attention to the contributions of merit and luck in the generation of a surplus and how they decide on its division. We find that subjects who randomly obtained an advantaged position pay less attention to information about true merit and retain more of the surplus. Both the attentional and behavioral patterns persist, although with smaller effect sizes, when dictators subsequently divide money between pairs of advantaged and disadvantaged subjects in the role of a benevolent judge. Moreover, attention has a substantial causal effect: forcing subjects to look for one second more at merit information relative to overall outcomes reduces the effect of having an advantaged position on allocations by about 25%. These findings open a new window on socio-economic cleavages in attitudes towards redistribution, and suggest that attention-based policy interventions may be effective in reducing polarized views on inequality.
Keywords: C91; D83; D87; 330; Redistribution; self-serving bias; attention; mouse-tracking; fairness